Ezetimibe and simvastatin combination inhibits and reverses the pro-inflammatory and pro-atherogenic effects of cream in obese patients. (August 2017) - Ghanim, Husam; Green, Kelly; Abuaysheh, Sanaa; Patel, Reema; Batra, Manav; Chaudhuri, Ajay; Makdissi, Antoine; Kuhadiya, Nitesh D; Dandona, Paresh
Abstract: Background and aims: Inflammation and postprandial lipemia are associated with increased cardiovascular disease. We investigated whether ezetimibe and simvastatin combination, a lipid lowering combination of simvastatin and ezetimibe, exerts an anti-inflammatory effect in the fasting state and after dairy cream intake. Methods: Twenty obese patients were randomized to either ezetimibe and simvastatin combination or placebo treatment for 6 weeks. All patients were asked to ingest 33 ml of dairy cream (300 Calories) at the beginning and at the end of intervention. Fasting and post-cream blood samples were obtained. Results: At 0 week, ingestion of cream induced significant increases in MNC expression of IL-1β (105 ± 18%), TNFα (97 ± 12%), CD68 (48 ± 8%), CD16 (141 ± 39%), MMP-9 (122 ± 31%), PECAM (66 ± 10%), TLR-4 (84 ± 11%) and TLR-2 (67 ± 9%) and in endotoxin (LPS) concentrations (49 ± 7%) ( p < 0.05). Ezetimibe and simvastatin combination treatment lowered fasting total cholesterol, LDLc and Lp(a) concentrations and Apo B/A1 ratio and suppressed the MNC expression of IL-1β and CD68 (by 21 ± 7 and 24 ± 10, p < 0.05) and the concentrations of LPS, CRP, FFA and IL-18 by 24 ± 7%, 32 ± 11%, 19 ± 8% 15 ± 4%, respectively, ( p < 0.05). Cream-induced increases in the expression of IL-1β, CD68, CD16, MMP-9, TNFα and PECAM were reduced in the ezetimibe and simvastatin combination group by 74 ± 15%, 68 ± 13%, 57 ± 13%, 64 ± 16%, 67 ± 14% and 45 ± 9%, respectively, while those of LPS and MMP-9 concentrations were reduced by 53 ± 9% and 38 ± 8%, respectively, compared to the increases at week 0 ( p < 0.05). There was a suppression of TLR-2 and TLR-4 expression by 21 ± 8% and 18 ± 7%, respectively, compared to 0-h baseline, after cream intake following ezetimibe and simvastatin combination treatment. Conclusions: Ezetimibe and simvastatin combination exerts a profound anti-inflammatory effect both in the fasting state and acutely after the ingestion of saturated fat. Highlights: Ezetimibe and simvastatin combination has anti-inflammatory effect in the fasting state of obese subjects. Ezetimibe and simvastatin combination attenuates pro-inflammatory effects of cream challenge in obese subjects. The anti-inflammatory effects includes suppression of atherogenic genes. Above changes occur in addition to reduction of fasting lipid concentrations.